Research into influence ofa capacitor connected in series to an asynchronous motor on the motor operation - Malyar, Vasyl; Hamola, Orest; Ryzhyi, Taras (Publishing House of Lviv Polytechnic National University, 2014)
Transmission of electrical energy to the place of consumption is accompanied by its loss, defined by the magnitude of currents that flow through thetransmission line. As the main load is inductive in nature, the currents in the line have reactive components, which provide additional energy losses in the line. For their reduction, a capacitor set is connected in parallel or in series to the consumer. The paper proposes a method and an algorithm of the research into the influence of capacitance value of the series capacitor set on the basic parameters and characteristics of asynchronous motors (AM). Unlike the classical equivalent circuits, the developed algorithm uses a mathematical model of AM in form of nonlinear equations system, which takes into account nonlinear dependences of flux linkage on currents and current displacement in squirrel-cage rotor bars. This allows the highly accurate determination of the electromagnetic parameters of the motor and varying (due to skin effect) resistances of the rotor winding, which significantly affect the occurrence of resonance. Пересилання електричної енергії до місця споживання супроводжується її втратами, які визначаються величиною струмів, що протікають по лініії. Оскільки основне навантаження має індуктивний характер, то струми в лінії мають реактивну складову, яка створює додаткові втрати електроенергії в лінії. Для їх зменшення використовують конденсаторні установки, які вмикають паралельно або послідовно зі споживачем. У роботі пропонується метод і алгоритм дослідження впливу значення ємності послідовно увімкнених конденсаторів на основні показники та характеристики асинхронних двигунів (АД). На відміну від класичних заступних схем, у розробленому алгоритмі використовується математична модель АД у вигляді нелінійної системи рівнянь, у якій враховуються нелінійні залежності потокозчеплень від струмів та витіснення струму в стержнях короткозамкненого ротора, що дає змогу з високою достовірністю визначати електромагнітні параметри двигуна та змінні внаслідок скін-ефекту активні опори обмотки ротора, які істотно впливають на появу резонансу.
Дослідження впливу послідовно увімкнених конденсаторів на роботу асинхронних двигунів
Keywords: asynchronous motors; reactive power; series capacitive compensation; static starting performance; saturation; skin effect